Influence of chemical treatment on quality of cut apple (cv. jonagored) - Rocha, A.M.C.N. (2011)
The quality of a new variety of apple, ‘Jonagored’, after peeling and cutting was evaluated during ten days of storage in air at 4C. The objective was to evaluate the shelf-life of apple cubes by detecting the limiting parameter and to test the influence of different chemical dips on the cut apple quality with the aim of extending shelf-life. Color, i.e. browning at the cut surface, was found to be the critical quality parameter determining the shelf-life of the cut apple to less than three days. There were no significant differences between the dip treatments in measurements of CIE values. When apple cubes were treated with ascorbic acid, ascorbic acid plus calcium chloride or ascorbic acid plus calcium chloride and citric acid, the 0.75% ascorbic acid dip was found to be the most effective preservation treatment in terms of reducing color change of the cut surface. Both 0.75% ascorbic acid and 0.75% ascorbic acid plus 0.75% calcium chloride inhibited the loss of firmness of apple cubes. When citric acid was added to the dip treatment, there were color changes similar to those of the control.